Finite Element Analysis of a Novel Temporary External Fixator (TEF) in Mandibular Reconstruction - Rungsan Chaiyachet; Surasith Piyasin; Weerayut Jina; Teerawat Paipongna; Apichart Boonma (Journal of Applied Science and Engineering)
This research examines temporary external fixators (TEF) with four screw plate configurations following segmental mandibulectomy. A new design for a screw plate accommodating 2 to 4 bicortical screws (2.4 mm each) is proposed. Biomechanical reliability is assessed using finite element analysis (FEA) and compared with the Schanz screws. A mandibular model was created with cortical and cancellous bones segmented by threshold method. The screw plate, designed in SolidWorks, featured a 12 mm inter-hole distance, 2.0 mm thickness, and 2.4 mm screws. Structural analysis was performed in ANSYS using literature-based mechanical properties. A mesh convergence test with a 0.33 mm mesh size and 1,005,000 elements had a solution time of 205 seconds, with a relative error under 0.161%. Static structural behavior of the Left Unilateral Molar Clench (LMOL) was also analyzed. The 3-screw plate showed superior biomechanical performance, with maximum von Mises stress at 293.38 MPa, von Mises strain at 23.57 m/mm, and total deformation at 0.5915 mm. Topology optimization revealed that the 50% mass configuration is the most effective among the 40% to 60% mass range. This configuration achieved a 2.31% decrease in Maximum von Mises stress, and a 16.99% reduction in total deformation.